EFFECTIVE COMMUNICATION SOLUTION POSITIVE MINIMIZES THE RISK IN MILK AND MILK PRODUCTS FOR CHILDREN BELOW 36 MONTHS AND PREGNANT WOMEN (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the effectiveness of positive communication solutions to reduce the risk inmilk and dairy products for children under 36 months and pregnant women.Subjects and methods: Community intervention study, with control group. Conduct activecommunication for 543 pregnant women, 543 mothers with children under 36 months (or caregivers)in 4 intervention wards. Evaluate the effectiveness of the intervention after 12 months, withcomparison of the control group.Results: The effectiveness of intervention with knowledge is 770.06%, practice is 235.5% (forpregnant women); for mothers with children under 36 months, knowledge is 376.9%, practice is260.9%. The intervention helped increase the use of milk and dairy products in pregnant womenand children under 36 months. The intervention has also resulted in a significant reduction in theincidence of diarrhea and malnutrition in young children.Conclusion: Active communication solutions have been proven effective in reducing the risk in milkand dairy products intended for children under 36 months and pregnant women.
Keywords: Active communication, food pollution, children, pregnant women.